Failure of Urological Implants in Spinal Cord Injury Patients due to Infection, Malfunction, and Implants Becoming Obsolete due to Medical Progress and Age-Related Changes in Human Body Making Implant Futile: Report of Three Cases - Subramanian Vaidyanathan; Bakul Soni; Gurpreet Singh; Peter Hughes; Fahed Selmi; Paul Mansour (Case Reports in Urology)
Any new clinical data, whether positive or negative, generated about a medical device should be published because health professionals should know which devices do not work, as well as those which do. We report three spinal cord injury patients in whom urological implants failed to work. In the first, paraplegic, patient, a sacral anterior root stimulator failed to produce erection, and a drug delivery system for intracavernosal administration of vasoactive drugs was therefore implanted; however, this implant never functioned (and, furthermore, such penile drug delivery systems to produce erection had effectively become obsolete following the advent of phosphodiesterase type 5 inhibitors). Subsequently, the sacral anterior root stimulator developed a malfunction and the patient therefore learned to perform self-catheterisation. In the second patient, also paraplegic, an artificial urinary sphincter was implanted but the patient developed a postoperative sacral pressure sore. Eight months later, a suprapubic cystostomy was performed as urethral catheterisation was very difficult. The pressure sore had not healed completely even after five years. In the third case, a sacral anterior root stimulator was implanted in a tetraplegic patient in whom, after five years, a penile sheath could not be fitted because of penile retraction. This patient was therefore established on urethral catheter drainage. Later, infection with Staphylococcus aureus around the receiver block necessitated its removal. In conclusion, spinal cord injury patients are at risk of developing pressure sores, wound infections, malfunction of implants, and the inability to use implants because of age-related changes, as well as running the risk of their implants becoming obsolete due to advances in medicine. Some surgical procedures such as dorsal rhizotomy are irreversible. Alternative treatments such as intermittent catheterisations may be less damaging than bladder stimulator in the long term.